New permanent bundle-branch block and long-term prognosis of patients with new onset ST-elevation myocardial infarction who underwent percutaneous coronary intervention - Yang, Yi; Wang, Jun; Wu, Bing; Xu, Yanan; Tang, Long; Jiang, Haibing; Wang, Benfang; Zhu, Tongjian (Frontiers in Physiology, 2022)
Aim: The aim of the study was to evaluate the potential predictive value of permanent RBBB and LBBB for longer-term prognosis in patients with new-onset STEMI who underwent percutaneous coronary intervention (PCI). Methods: Patients with new-onset STEMI that underwent emergency PCI at our department from June 2012 to September 2020 were included in the study. Gensini score (GS) was employed to evaluate the severity of coronary lesions. The primary endpoint of the study was the occurrence of MACCEs, the composite of cardiac mortality, recurrence of myocardial infarction, stent thrombosis, cardiac shock, stroke, or revascularization. The secondary endpoint was all-cause mortality. Results: Out of the 547 patients, 29 patients had new-onset permanent LBBB, 51 patients had new-onset permanent RBBB, and 467 patients had no bundle-branch block (BBB). The occurrence of no BBB, new permanent LBBB, or RBBB was not associated with the severity of coronary lesions as evaluated by the GS. After follow-up at an average of 43.93 months, MACCEs occurred in 43 patients. Kaplan-Meier analysis showed that patients with new-onset RBBB were at greater risk for MACCEs compared to those with new onset LBBB（ χ2 = 5.107, P = 0.021 ). And the occurrence of new permanent RBBB and LBBB was independently correlated with increased risk of MACCEs. The adjusted hazard ratios (HRs) were 6.862 [95% confidence interval ( CI ), 3.764 to 12.510] for the new-onset permanent RBBB and 3.395 ( 95% CI, 1.280 to 9.005 ) for LBBB, compared to those with no BBB, respectively ( both P < 0.05 ). Conclusions: New onset permanent RBBB in patients with new onset STEMI who underwent PCI may be associated with poor long-term prognosis.